ANALISIS PEMBELAJARAN DARING PADA MATA PELAJARAN SEJARAH PEMINATAN KELAS XI IPS 1 SMA ISLAMIYAH PONTIANAK - Khairunisa, Lia; Ulfah, Maria; Putri, Astrini Eka (Universitas Tanjungpura, 2022)
This study aimed to investigate how the online learning on history subject was planned and implemented. This study used descriptive qualitative approach. Data collection techniques used were observation, interviews, and documentation. The researcher used a purposive sampling technique in which the research participants were the head of curriculum teacher, history subject teacher, and class XI Social Sciences 1 students at SMA Islamiyah Pontianak . The results of this study were lesson plans prepared by the teachers, such as learning tools, learning materials and the media used. The implementation of learning at SMA Islamiyah Pontianak had been prepared and carried out in accordance with the lesson plans prepared. Online learning at SMA Islamiyah used the following media:WhatsApp, Google Classroom, and Google Meet applications. In the implementation of online learning, some factors occurred: there was lack of awareness by students in online learning, some students were motivated, and there was lack of supervision from parents. It was concluded that the implementation of online learning occurred in sample research was not carried out well.